Feasibility of Online High-Intensity Interval Training (HIIT) on Psychological Symptoms in Students in Lockdown During the COVID-19 Pandemic: A Randomized Controlled Trial - Philippot, Arnaud; Moulin, Pauline; Charon, Marie-Hélène; Balestra, Costantino; Dubois, Vincent; de Timary, Philippe; De Volder, Anne; Bleyenheuft, Yannick; Lambrechts, Kate (Frontiers in Psychiatry, 2022)
Objective: We aimed to evaluate the effects of an online High-Intensity Interval Training (HIIT) program on clinical psychological symptoms in higher education students in the context of the COVID-19 pandemic lockdown. Materials and methods: During the lockdown, 30 students aged 18-25 years, who had been screened previously with a cut-off score ≥ 5 in the Generalized Anxiety Disorder-7 (GAD-7) questionnaire, were randomly assigned to either the four-week HIIT program with three sessions per week conducted through online videos, or a no-intervention control group. The primary outcome was the 21-items Depression, Anxiety, and Stress Scale (DASS-21). Evaluation and intervention were performed in compliance with social distancing rules. Results: Two participants in the HIIT were lost to follow-up, leaving 13 participants versus 15 in the control group. The Mann-Whitney test demonstrated a significant (group x time, p-value=0.046) reduction of clinical stress symptoms and a trend (group x time, p-value = 0.08) towards reduction of clinical depression symptoms, both favoring the HIIT group. No significant (group x time, p-value=0.118) interaction was found for anxiety symptoms. We observed high adherence (87%) with the HIIT intervention delivered by online videos. Conclusion: The HIIT program reduced clinical stress and depressive symptoms, and thus shows promise for broader application among higher education students during the present lockdown necessitated by the global COVID-19 health crisis.